Environmental surface and air contamination in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) patient rooms by disease severity. Issue 4 (December 2020) - Nakamura, Keiji; Morioka, Shinichiro; Kutsuna, Satoshi; Iida, Shun; Suzuki, Tadaki; Kinoshita, Noriko; Suzuki, Tetsuya; Sugiki, Yuko; Okuhama, Ayako; Kanda, Kohei; Wakimoto, Yuji; Ujiie, Mugen; et al.
Summary: Background: The coronavirus disease 2019 (COVID-19) continues to spread around the world. In addition to community-acquired infections, nosocomial infections are also a major social concern. The likelihood of environmental contamination and transmission of the virus based on disease severity is unknown. Methods: We collected nasopharyngeal, environmental and air samples from patients with COVID-19 admitted to the National Centre for Global Health and Medicine between January 29 th and February 29 th, 2020. The patients were classified by severity of disease. The collected samples were tested using severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) real-time reverse transcription polymerase chain reaction (real-time RT-PCR). Results: SARS-CoV-2 was not detected in a subset of 11 air samples. Of the 141 environmental samples collected from three patient bays and two single rooms, four samples tested positive for SARS-CoV-2 by real-time RT-PCR. Detections were made on the surface of a stethoscope used in the care of a patient with severe disease, on the intubation tube of a patient classified as critical (and on ventilator management), and on the surface of a gown worn by the nurse providing care. Conclusions: Regardless of the patients' disease severity, SARS-CoV-2 was detected on very few environmental surfaces. However, detection of SARS-CoV-2 on stethoscopes used in the care of multiple patients and on the surface of gowns worn by clinical staff indicates that medical devices may be linked to the spread of infection.